Protein engineering of cytochrome p450(cam) (CYP101) for the oxidation of polycyclic aromatic hydrocarbons. - Harford-Cross, C; Carmichael, AB; Allan, F; England, P; Rouch, D; Wong, L (2000)
Mutations of the active site residues F87 and Y96 greatly enhanced the activity of cytochrome P450(cam) (CYP101) from Pseudomonas putida for the oxidation of the polycyclic aromatic hydrocarbons phenanthrene, fluoranthene, pyrene and benzo[a]pyrene. Wild-type P450(cam) had low (<0.01 min(-1)) activity with these substrates. Phenanthrene was oxidized to 1-, 2-, 3- and 4-phenanthrol, while fluoranthene gave mainly 3-fluoranthol. Pyrene was oxidized to 1-pyrenol and then to 1,6- and 1,8-pyrenequinone, with small amounts of 2-pyrenol also formed with the Y96A mutant. Benzo[a]pyrene gave 3-hydroxybenzo[a]pyrene as the major product. The NADH oxidation rate of the mutants with phenanthrene was as high as 374 min(-1), which was 31% of the camphor oxidation rate by wild-type P450(cam), and with fluoranthene the fastest rate was 144 min(-1). The oxidation of phenanthrene and fluoranthene were highly uncoupled, with highest couplings of 1.3 and 3.1%, respectively. The highest coupling efficiency for pyrene oxidation was a reasonable 23%, but the NADH turnover rate was slow. The product distributions varied significantly between mutants, suggesting that substrate binding orientations can be manipulated by protein engineering, and that genetic variants of P450(cam) may be useful for studying the oxidation of polycyclic aromatic hydrocarbons by P450 enzymes.